2016
DOI: 10.1177/1077801216651339
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Coercion Practices Among Undergraduate Male Recreational Athletes, Intercollegiate Athletes, and Non-Athletes

Abstract: Prior research shows that male intercollegiate athletes are at risk for perpetrating sexual violence. Whether this risk extends to male recreational athletes has not been explored. This study assessed associations between attitudes toward women, rape myth acceptance, and prevalence of sexual coercion among 379 male, undergraduate recreational and intercollegiate athletes and non-athletes. Our analyses showed significant differences between the responses of athletes and non-athletes for all dependent variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 34 publications
(54 reference statements)
1
59
1
1
Order By: Relevance
“…These issues are partly due to the fact that different types of tactics used by perpetrators to obtain sex with unwilling partners have not been adequately defined or measured [ 59 , 60 , 61 ]. By using victim reports on unwanted sexual activity experienced by victims [ 34 , 38 , 46 , 56 , 62 , 63 , 64 , 65 ], the methods used by perpetrators to obtain sex from unwilling partners [ 37 , 45 , 59 , 66 , 67 , 68 , 69 , 70 , 71 ], or studies examining both victimization and perpetration behaviors [ 39 , 72 , 73 ], sexual coercion has been defined in several ways.…”
Section: Sexual Coercionmentioning
confidence: 99%
“…These issues are partly due to the fact that different types of tactics used by perpetrators to obtain sex with unwilling partners have not been adequately defined or measured [ 59 , 60 , 61 ]. By using victim reports on unwanted sexual activity experienced by victims [ 34 , 38 , 46 , 56 , 62 , 63 , 64 , 65 ], the methods used by perpetrators to obtain sex from unwilling partners [ 37 , 45 , 59 , 66 , 67 , 68 , 69 , 70 , 71 ], or studies examining both victimization and perpetration behaviors [ 39 , 72 , 73 ], sexual coercion has been defined in several ways.…”
Section: Sexual Coercionmentioning
confidence: 99%
“…IHE have begun targeting student-athletes as the source of campus violence, primarily surrounding sexual assaults. There have been studies that suggest a connection exists between athletic participation and committing acts of sexual violence (Boeringer, 1996(Boeringer, , 1999Forbes et al, 2006;Frintner & Rubinson, 1993;Koss & Gaines, 1993;McCray, 2015;McMahon, 2011;Murnen & Kohlman, 2007;Young et al, 2017). Both research and media reports of sexually violent crimes Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Research attempting to correlate athletic participation with the propensity to be sexually violent is both vast and inconsistent. Many studies suggest a connection exists between athletic participation and sexual violence (Boeringer, 1996(Boeringer, , 1999Forbes et al, 2006;Frintner & Rubinson, 1993;Koss & Gaines, 1993;McCray, 2015;McMahon, 2011;Murnen & Kohlman, 2007;Young et al, 2017) while another body of scholarship has found no such connection exists (Caron et al, 1997;Crosset, Benedict, & McDonald, 1995;Gidycz, Warkentin, & Orchowski, 2007;Smith & Stewart, 2003). Moreover, researchers have questioned the findings and assertions between athletic participation and sexual violence due to methodological concerns (Crosset, 1999;Kimble, Russo, Bergman, & Galindo, 2010;Koss & Gaines, 1993).…”
Section: Sexual Violence and Intercollegiate Student-athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 15 years, only two studies sought to question whether male student-athletes are more likely to perpetrate sexual assault (Sawyer, Thompson, & Chicorelli, 2002;Young, Desmarais, Baldwin, & Chandler, 2017) and many studies have documented the generally positive effects of sexual assault prevention programming with student-athletes (Foubert & Perry, 2007;Jackson & Davis, 2000;McMahon & Farmer, 2009;Moynihan & Banyard, 2008;Moynihan, Banyard, Arnold, Eckstein, & Stapleton, 2010). Most recently, Young and colleagues (2017) discovered that intercollegiate student-athletes and recreational athletes exhibited similar rates of sexual coercion, with notably higher rates than non-athletes.…”
Section: Introductionmentioning
confidence: 99%